Pemanfaatan Museum Perjuangan Lampung Timur Sebagai Salah Satu Sumber Belajar Sejarah - RACHMEDITA, VALENSY; Yustina Sri Ekwandari; Ema Agustina; Aprilia Triaristina (CHRONOLOGIA, 2026)
A museum is an institution that functions as a place for preserving, researching, and collecting objects related to history, culture, and science. The utilization of learning resources is one of the essential skills that educators must possess in order to make effective use of available resources—whether simple or complex without neglecting their usefulness or relevance to the learning materials and objectives. In history learning activities, museums play an important role in helping students understand life and culture. One museum with significant historical value is the Lampung Timur Struggle Museum. This museum not only stores historical artifacts but also functions as a center for education, documentation, and the strengthening of local identity.  The aim of this study is to encourage students to utilize the museum as a direct learning resource, enabling them to better understand the meaning of history. The research method employed in this study is descriptive. The findings indicate that museums play an important role as one of the historical learning resources for students. They can be used to enhance students’ understanding of historical events, foster awareness of local identity, and strengthen the values of nationalism in the process of history learning.